LEPTIN INCREASES IN VITRO DEVELOPMENTAL POTENTIAL OF PREPUBERTAL AND PUBERTAL DECCANI EWE OOCYTES - KESHRAWANI, S; ARUNA KUMARI, G; RAM SINGH, L (The Indian Journal of Animal Reproduction, 2022)
The impact of leptin addition (0, 10, 20, 50 and 100 ng/ml) in maturation media on Deccani ewe oocytes(prepubertal, 383; pubertal, 376) was investigated during non-breeding season. The cumulus oocyte complexexpansion and oocytes at M-II stage with extrusion of first polar body in prepubertal (63.8±1.5% and 61.1±2.5%,respectively) and pubertal (68.2±1.3% and 66.2±2.%, respectively) ewes was higher (p
Keywords: COCs; Ewe; Leptin,; M-II stage; Oocytes